Pengembangan Modifikasi Permainan Kecil Untuk Anak Tunagrahita Di SLB Koto Agung Sungai Duo Dharmasraya - Sigit Prayogi Anugrah; Zuhar Ricky; Dian Estu Prasetyo (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2023)
This research was motivated by students who have poor motor skills, because students at SLB Koto Agung have never participated in a sports learning program to improve motor skills, especially mentally retarded children who have difficulty learning because they have weak memories. The cognitive and mental development of mentally retarded children requires stimulation that is given regularly and systematically by teachers. This type of research is research and development (R&D) using the ADDIE model which consists of 5 stages: analyze, design, development, implementation, and evaluation. Validation tests were carried out by 3 validators, practicality tests by PJOK teachers and 10 students, and effectiveness tests through ball throwing and catching tests. The results showed that the small game model of throwing and catching obtained an average validity of 93.3% (very valid), practicality by teachers 90% (very practical), practicality by students 79.25% (practical), and effectiveness 80% (effective). Thus, this small game modification model has met the criteria of valid, practical, and effective so that it is suitable for use in PJOK learning at SLB.